Embryo Development and Effects of Temperature, Salinity, and Light Intensity on Egg Hatching of Calanoid Copepod Bestiolina amoyensis (Calanoida: Paracalanidae) - Wang, Shuhong; Wang, Lin; Wang, Yuyue; Chen, Yun; Chen, Jinmin; Chen, Nan (Frontiers in Marine Science, 2022)
Bestiolina amoyensis distributes in subtropical inshore waters across the Pacific Ocean, with a relatively long reproductive lifespan and high intrinsic population increase rate compared with other small paracalanid species, which makes it a good candidate to develop culture techniques for hatchery larval rearing. However, the reproductive biology of this subtropical broadcast spawning species is still largely unknown. The present investigation provides the first published data on the embryo development and effects of different light intensities (0, 500, and 1,000 lx), temperatures (16°C, 18°C, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, and 34°C), and salinities (22, 24, 26, 28, 30, 32, and 34 psu) on hatching success rates of B. amoyensis. The same batch of eggs were collected from gravid females to observe their embryonic development and incubated under designed light intensities, temperatures, and salinities. Results showed that the whole embryonic development of B. amoyensis lasted, on average, 6 h and 40 min at 26°C, and egg hatching time of B. amoyensis shortened exponentially with the increasing temperature. The highest egg hatching rate (100%) was recorded from the 0-lx treatment, indicating that the dark condition was favorable for the egg incubation of B. amoyensis. The optimum temperature and salinity range for the hatching success of B. amoyensis was 22°C–30°C (above 94%) and 22–34 psu salinity (above 88%), respectively, indicating that B. amoyensis had wide adaptability to temperature and salinity. Light and too low or high temperature leads to abnormal embryonic development and malformed nauplii. The relatively wide adaptability to temperature and salinity and fast embryo development also suggests that B. amoyensis was a good candidate as live feed for hatchery larval rearing.